Esophageal Stenosis as a Rare Mode of Revelation of Hereditary Epidermolysis Bullosa: Report of Three Cases - ELMANJRA, Chama; Tadili, Houda; Bounouar, Ibtissam; El Azzam, Naima; Nacir , Oussama; Lairani, Fatima Ezzahra; Aboudourib, Maryam; Ait Errami, Adil; Oubaha, Sofia; Hocar, Ouafa; Amal, Said; Samlani, Zouhour; et al. (International Journal of Innovative Research in Medical Science, 2023)
Dystrophic epidermolysis bullosa (DEB) is a heterogeneous group of rare genodermatoses with multiple variants and multi-organ involvement, including digestive system with esophageal stenosis. We describe in this paper 3 unusual cases of hereditary epidermolysis bullosa revealed by dysphagia. The first one is a 77-year-old man admitted with chronic dysphagia, cutaneous erosions and a complete loss of fingers and toenails. Gastroscopy with skin biopsies and barium swallow confirmed a hereditary epidermolysis bullosa. He was treated by pneumatic dilatation. The second case is a 60-year-old female admitted because of dysphagia. She was on good condition but had lingual erosions and anonychia affecting fingernails and toenails, with esophageal stenosis. The skin biopsy confirmed the DEB. She was treated successfully with pneumatic dilatation. The third case is a 15-year-old male who was transferred to our department for management of esophageal stenosis. The physical examination showed malnutrition and dehydration with bullous lesions and anonychia. The diagnostic of DEB was confirmed and he was treated by pneumatic dilatation. Dysphagia can rarely reveal an esophageal stenosis complicating a DEB, and can be treated successfully by pneumatic dilatation.